Numerical Simulation of Slope–Gully–Stream Sediment Transport Process with Water and Gravity Erosion - Liu, Yan; Yang, Zhenyu; Wang, Xiekang (Frontiers in Earth Science, 2022)
Soil erosion has become a global problem with serious consequences. It is the source of sediment in rivers, and the subsequent sediment transport is important. Water erosion and gravity erosion, as common forms of soil erosion, have different subsequent sediment transport processes. Numerical simulations can reflect these processes well under different sediment yield types. This study applied the computational fluid dynamics and discrete element method (CFD-DEM) to examine the sediment transport following water erosion and gravity erosion. During the sediment transport process, the solid-phase particles in the gravity erosion case move at a greater speed during the initial stage. In the case of water erosion, a decrease in particle velocity on the slope occurs due to the accumulation of particles. The streamwise velocity distribution of the liquid phase conforms to the logarithmic distribution before the sediment transport process starts. Influenced by the solid-phase particles, the flow velocity near the bottom decreases significantly. The sediment transport rate peak in gravity erosion cases is greater than that in water erosion cases. Furthermore, in water erosion cases, when the slope is steep, there is no peak in the sections located at the inlet and outlet of a gully. The sediment transport rate in river sections shows a step form in the declining process.